Unmet mental health needs in the general population: perspectives of Belgian health and social care professionals - Rens, Eva (Int J Equity Health, 2020)
BACKGROUND: An unmet mental health need exists when someone has a mental health problem but doesn’t receive formal care, or when the care received is insufficient or inadequate. Epidemiological research has identified both structural and attitudinal barriers to care which lead to unmet mental health needs, but reviewed literature has shown gaps in qualitative research on unmet mental health needs. This study aimed to explore unmet mental health needs in the general population from the perspective of professionals working with vulnerable groups. METHODS: Four focus group discussions and two interviews with 34 participants were conducted from October 2019 to January 2020. Participants’ professional backgrounds encompassed social work, mental health care and primary care in one rural and one urban primary care zone in Antwerp, Belgium. A topic guide was used to prompt discussions about which groups have high unmet mental health needs and why. Transcripts were coded using thematic analysis. RESULTS: Five themes emerged, which are subdivided in several subthemes: (1) socio-demographic determinants and disorder characteristics associated with unmet mental health needs; (2) demand-side barriers; (3) supply-side barriers; (4) consequences of unmet mental health needs; and (5) suggested improvements for meeting unmet mental health needs. CONCLUSIONS: Findings of epidemiological research were largely corroborated. Some additional groups with high unmet needs were identified. Professionals argued that they are often confronted with cases which are too complex for regular psychiatric care and highlighted the problem of care avoidance. Important system-level factors include waiting times of subsidized services and cost of non-subsidized services. Feelings of burden and powerlessness are common among professionals who are often confronted with unmet needs. Professionals discussed future directions for an equitable mental health care provision, which should be accessible and targeted at those in the greatest need. Further research is needed to include the patients’ perspective of unmet mental health needs.